The Importance of Digital Financial Literacy in Cyrptocurrency Investment: A Qualitative Study - Fadli, Jul Aidil (Jurnal Informatika Ekonomi Bisnis, 2024)
This research aims to examine the role of digitial financial literacy in cryptocurrency investment activities. This research is a qualitative study through interviews with two key informants who have qualified experience in the field of investing in cryptocurrency. The study shows that digital financial literacy plays an important role in investing, especially in the technology-driven cryptocurrency space. Therefore, it is important for investors to have a good understanding and experience before choosing cryptocurrencies as part of their investment portfolio. From a government perspective, it is important to spread the understanding that financial literacy is an important part of investing. These findings also support the continuation of the government's programme to make digital financial literacy part of the roadmap in Indonesia's National Financial Literacy Strategy.